KESINAMBUNGAN AJARAN AL-QUR’AN DAN HADITS DALAM PENGEMBANGAN PENDIDIKAN ISLAM - YUSEFA HELFY PRASTIKA; MUHAMMAD FATHONI (STIT DARUL ULUM KOTABARU, 2023)
Al-Qur'an and hadith are life guidelines for Muslims, so that in them there are many teachings in the form of life instructions for Muslims so that they can create good life in this world and the hereafter. Al-Qur'an and hadith play an important role as a source of knowledge and knowledge in Islam. The teachings contained in the Koran and hadith contain matters of faith, sharia, and morals. Along with the growth of the times, of course, Islamic education as a must be growing to strengthen Islamic knowledge by referring to the Qur'an and hadith. By seeking information in advance from several journals and books about the teachings of the Qur'an and hadith and their relation to the development of Islamic education, it is hoped that this paper can help someone who will develop Islamic education that the teachings contained in the Al- Qur'an This an and hadith are closely related to the development of Islamic education and are very helpful for the development of Islamic education in the world.